Enhancing Critical Thinking Through Problem-Solving Activities in English Lessons - Amir Abdulhussein Hashim Albuhmedee (International Journal of Language and Literary Studies, 2025)
This is a systematic literature review that seeks to explore how problem-solving activities can be used to help in teaching the English language (ELT) to foster critical thinking. The review summarizes recent empirical research (2020 - 2025) regarding problem-based learning (PBL), inquiry-based learning, and collaborative problem-solving. Among the factors that most significantly contribute to the attainment of this objective are the promotion of analytical reasoning, self-regulation, and engagement through authentic, contextually relevant tasks. It was found that scaffolding, collaboration with peers, and the authenticity of problem contexts were the key components of critical thinking. Besides confirming that problem-solving activities have a positive effect on the cognitive and language abilities of students, this review offers practical ideas to educators on how they can make problem-solving tasks more effective in terms of both design and implementation. The review also explores the best strategies for facilitating critical thinking through problem-solving, which can be a great source of help to English teachers who wish their students to develop higher-order cognitive skills. Nevertheless, time limitations, teacher readiness and resource shortages are still obstacles to universal deployment.